Rendimendo de capturas do Carangueijo-Uçá (Ucides cordatus, Linnaeus, 1763) e Guaiamum (Cardisoma guanhumi, Latreille, 1828) em Sergipe, Brasil - Feitosa, Felipe Dias (2015)
Small-scale fisheries is a very important activity for the traditional communities’ survival. In Sergipe, it is practiced mainly in estuarine areas, mostly by the manual gathering of brachyurans, involving men and women in the process of capture, processing and commercialization of the production. Studies seeking evaluate the evolution of the catches, fishing effort and Catch per Unit Effort – CPUE of brachyurans, mainly about the land crab, captured by the small-scale fishermen of Sergipe are inexistent or have not been published yet. Considering the activity importance to the survival of these populations, the objective of this paper was to analyze the catches, fishing effort and CPUE of the Sergipe’s small-scale fisheries of brachyurans. Catch and fishing effort data of the mangrove crab (Ucides cordatus, Linnaeus, 1763) and land crab (Cardisoma guanhumi, Latreille, 1828) were used for the calculation of CPUE, collected by the Participative Monitoring Project of Fishing Landings (PMPDP), between 2010 and 2014 on Sergipe’s coast. It was observed growth trends in the CPUE of the mangrove crab almost in every community studied. This growth was probably due trends of changings in finishing effort caused by the adoption of methods of capture more efficient than the traditional arm gathering, like, the use of the redinha or tapamento methods. In relation to the land crab, a reduction of the CPUE was observed probably due the reduction of the resource’s abundance at the Sergipe’s estuaries.